2017
DOI: 10.1007/s11999-016-4810-7
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Functional Results and Complications With Long Stem Hemiarthroplasty in Patients With Metastases to the Proximal Femur?

Abstract: Background Traditional treatments for pathological fractures of the proximal femur resulting from metastatic bone disease include fixation with intramedullary nailing supplemented with polymethylmethacrylate, osteosynthesis with a plate-screw construct and polymethylmethacrylate, or endoprosthetic reconstruction. Despite the frequent practice of these treatments, treatment outcomes have not been rigorously compared. In addition, very few studies examine specific approaches to endoprosthetic reconstruction such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…However, all prognostic models except OPTIModel included multiple myeloma and lymphoma it the assessment of patient survival. These haematological malignancies cause pathological fractures of the femur requiring orthopaedic management [3], [13], [14], [15], [16], [35], [36]. This analysis included multiple myeloma and lymphoma primary cancer types in the femoral MBD patient dataset.…”
Section: Discussionmentioning
confidence: 99%
“…However, all prognostic models except OPTIModel included multiple myeloma and lymphoma it the assessment of patient survival. These haematological malignancies cause pathological fractures of the femur requiring orthopaedic management [3], [13], [14], [15], [16], [35], [36]. This analysis included multiple myeloma and lymphoma primary cancer types in the femoral MBD patient dataset.…”
Section: Discussionmentioning
confidence: 99%
“…These scores are very comparable and it may be that no benefit from further rehabilitation is gained over time or, more likely, the ceiling effect of the MSTS score is achieved already 6 months postoperatively, and therefore other questionnaires should be used instead in future studies to address gain in functional outcome over time. Peterson et al [31] have a similar way of presenting their data, regarding patients undergoing long-stemmed hemiarthroplasty for MBDf, and report above or below one year follow-up, but again not with exact follow-up period in these two categories. They observe a gain in MSTS score over time with an average MSTS score of 27 for patients followed for more than one year after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The MSTS score did increase gradually over the first six months postoperatively for the endoprosthesis group, indicating the potential for improvement over time. Most studies reporting the MSTS score in MBDf patients undergoing surgery report the score as an average at clinical follow-up at any time after surgery [29], [30], [31], and this bias the outcome, as we do not know how many patients were scored 2 years after surgery or 2 weeks after surgery. Harvey et al [29] found no statistically significantly difference in MSTS score comparing treatment with internal fixation to endoprosthesis, but they also report that patients having internal fixation was followed on average of 20 months postoperatively compared to 14 months for the endoprosthesis group, allowing for further rehabilitation time for the internal fixation group, which potentially bias their reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Peterson et al evaluated the outcomes after utilization of a long stem hemiarthroplasty in the setting of bony metastasis of the proximal femur and found fair levels of postoperative function. 61 Steensma et al reported a significantly lower treatment failure rate and fewer revisions requiring implant exchange in patients who underwent endoprosthetic reconstruction when compared with open reduction-internal fixation and intramedullary nailing. 62 Janssen et al performed a retrospective study on the complications after the surgical management of proximal femoral metastasis.…”
Section: Metastatic Diseasementioning
confidence: 99%